1991
DOI: 10.1046/j.1537-2995.1991.31191096182.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of human immunodeficiency virus by gamma radiation and its effect on plasma and coagulation factors

Abstract: The inactivation of HIV by gamma-radiation was studied in frozen and liquid plasma; a reduction of the virus titer of 5 to 6 logs was achieved at doses of 5 to 10 Mrad at -80 degrees C and 2.5 Mrad at 15 degrees C. The effect of irradiation on the biologic activity of a number of coagulation factors in plasma and in lyophilized concentrates of factor VIII (FVIII) and prothrombin complex was examined. A recovery of 85 percent of the biologic activity of therapeutic components present in frozen plasma and in lyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 44 publications
5
32
0
Order By: Relevance
“…Furthermore, we found that gamma irradiation degraded viral structural proteins and genetic materials and damaged viral particles, which resulted in viral inactivation. Although gamma irradiation seems impractical to eliminate the virus contaminants in fresh produce by the FDA-approved irradiation dose limits, this technology may be practical to inactivate viruses in other foods and to sterilize medical devices, ophthalmic solutions, pharmaceuticals, tissue culture sera, animal waste, and municipal sewage (17,28,29,55,57,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that gamma irradiation degraded viral structural proteins and genetic materials and damaged viral particles, which resulted in viral inactivation. Although gamma irradiation seems impractical to eliminate the virus contaminants in fresh produce by the FDA-approved irradiation dose limits, this technology may be practical to inactivate viruses in other foods and to sterilize medical devices, ophthalmic solutions, pharmaceuticals, tissue culture sera, animal waste, and municipal sewage (17,28,29,55,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to our study, it was thought that damage of viral genetic material is the major target for virus inactivation (28,29,55,57,58). Therefore, gamma irradiation is widely used as means to prepare inactivated viral vaccines (12,42).…”
Section: Discussionmentioning
confidence: 99%
“…Gamma irradiation seems not to affect some tests, but the intensity necessary to inactivate viruses is usually not available in hospitals, and the procedure decreases activities of enzymes and results of coagulation tests (3,5 ). Heat inactivation can be done simply in a biological safety cabinet with a waterbath at 60°C, treating samples for 30 min to inactivate corona viruses or for 60 min to inactivate Lassa, Ebola, or Marburg viruses (3 ).…”
mentioning
confidence: 99%
“…Many factors can modify the sensitivity of pathogens microorganisms to ionizing radiation, including the temperature of irradiation. For example, the reduction of HIV virus was achieved with a dose of 50-100 kGy in frozen plasma (-80 o C), and with 25 kGy at 15 o C (Hiemstra et al, 1991). The D 10 value for HIV-1 irradiated at room temperature was 7.2 kGy, and 8.3 kGy at -80 o C (Hernigou et al, 2000).…”
Section: Gamma Sterilization Of Human Tissue Graftsmentioning
confidence: 99%